2013
DOI: 10.1603/en13070
|View full text |Cite
|
Sign up to set email alerts
|

Life History Comparison of Two Green Lacewing SpeciesChrysoperla johnsoniandChrysoperla carnea(Neuroptera: Chrysopidae)

Abstract: We investigated the life histories of two green lacewing species, Chrysoperla johnsoni Henry, Wells, and Pupedis from western North America, and Chrysoperla carnea (Stephens) (Neuroptera: Chrysopidae) from western Europe in the laboratory. There were both similarities and differences in their life history characteristics. C. johnsoni exhibited a significantly longer developmental time for egg, first instar, and pupal stage than C. carnea. C. carnea exhibited a significantly shorter egg to adult developmental t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…The r m calculation of C. rufilabris agrees closely with Jokar & Zarabi (2012) when C. carnea was reared under laboratory conditions (r m values of 0.074, 0.162, and 0.185) and fed with different media. Amarasekare & Shearer (2013) reported similar r m values calculated for C. carnea and Chrysoperla johnsoni Henry (Neuroptera: Chrysopidae) of 0.161 and 0.132, respectively. This laboratory experiment provides information needed to understand the effect of B. bassiana on C. rufilabris.…”
Section: Discussionsupporting
confidence: 53%
“…The r m calculation of C. rufilabris agrees closely with Jokar & Zarabi (2012) when C. carnea was reared under laboratory conditions (r m values of 0.074, 0.162, and 0.185) and fed with different media. Amarasekare & Shearer (2013) reported similar r m values calculated for C. carnea and Chrysoperla johnsoni Henry (Neuroptera: Chrysopidae) of 0.161 and 0.132, respectively. This laboratory experiment provides information needed to understand the effect of B. bassiana on C. rufilabris.…”
Section: Discussionsupporting
confidence: 53%
“…They are commonly found in pear orchards in Oregon. Chrysoperla johnsoni Henry, Wells and Pupedis is one of the most common green lacewing species found in the western United States, including Washington, Oregon, Idaho, California and Arizona [ 25 , 26 , 27 , 28 ]. In this study, we found continuous abundance of Chrysoperla sp.…”
Section: Discussionmentioning
confidence: 99%